2016
DOI: 10.1002/etc.3433
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of phenanthrene toxicity in the soil invertebrate, Enchytraeus crypticus

Abstract: Polycyclic aromatic hydrocarbons (PAHs) continue to cause environmental challenges as a result of their release into the environment by a great variety of anthropogenic activities and their accumulation in soils. Studies were conducted on the toxicological effect of the model PAH phenanthrene using the soil invertebrate model Enchytraeus crypticus at the individual, tissue, and molecular levels. Animals were exposed for 2 d and 21 d to phenanthrene concentrations corresponding to the (previously estimated) 3-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Due to their lipophilic nature, PAHs may accumulate in organisms. The cytochrome P450 oxygenases and transferases of the phase I and phase II biotransformation systems of organisms can transfer PAHs into more water-soluble metabolites, which are eliminated from the body by transporters. , PAHs and their metabolites are directly harmful to soil communities by accumulating in soil biota . The toxicokinetics of PAHs has been investigated in both aquatic and terrestrial organisms, but with most focus on aquatic invertebrates and fish. Much less is known on the uptake and elimination of PAHs in terrestrial invertebrates, such as the enchytraeid, Enchytraeus albidus …”
Section: Introductionmentioning
confidence: 99%
“…Due to their lipophilic nature, PAHs may accumulate in organisms. The cytochrome P450 oxygenases and transferases of the phase I and phase II biotransformation systems of organisms can transfer PAHs into more water-soluble metabolites, which are eliminated from the body by transporters. , PAHs and their metabolites are directly harmful to soil communities by accumulating in soil biota . The toxicokinetics of PAHs has been investigated in both aquatic and terrestrial organisms, but with most focus on aquatic invertebrates and fish. Much less is known on the uptake and elimination of PAHs in terrestrial invertebrates, such as the enchytraeid, Enchytraeus albidus …”
Section: Introductionmentioning
confidence: 99%
“…Phenanthrene (PHE) is the smallest PAHs with carcinogenic characteristics, which is used as a degradation study model (Roelofs et al . 2016). In this context, different researches have identified: new bacteria with high degradation activity of PAHs (Toledo et al .…”
Section: Introductionmentioning
confidence: 99%
“…2014; Roelofs et al . 2016). Based on this, in this work, different fungal strains of the phylum Ascomycota from the soil of the ‘La Escondida’ lagoon in Reynosa, Mexico were isolated and characterized to determine their ability to degrade one of the main PAHs, PHE.…”
Section: Introductionmentioning
confidence: 99%
“…Duan et al [164] found changes in ROS-scavenging enzymes (superoxide dismutase and catalase) in E. fetida after 14 days of exposure to benzo-[a]pyrene, but not lipid peroxidation at concentrations below 500 mg kg À1 d.w. For the same species and chemical, Ye et al [168] denoted an increase in superoxide dismutase and peroxidase activities and failure to reach a new homeostasis status after 56 days at 10 mg kg À1 d.w. Glutathione S-transferases alterations were reported for phenanthrene and fluorene in E. fetida [169]. Recent OMICS have highlighted important differences in toxicity pathways elicited by PACs to soil organisms, as shown by Roelofs et al [170] for F. candida and E. crypticus after exposure to phenanthrene. Whereas no strong induction of biotransformation pathways was observed in E. crypticus, upregulation of genes encoding all phases of biotransformation/detoxification (I/II/III) was found in F. candida.…”
Section: Effect Of Polycyclic Aromatic Compounds At Sub-organism Levelmentioning
confidence: 92%